ECONOMICS OF SMALL ONION IS IT FEASIBLE TO THE PRODUCERS? - A CASE STUDY - Rajendran, (International Journal of Research -GRANTHAALAYAH, 2017)
While the farming community is facing a heavy loss in the cultivation of crops such as paddy, sugarcane and turmeric, vegetables, particularly the small onions, give them a significant return. The income from the vegetables helps the farmers to meet their living expenses. This study is purposefully conducted as termed as Case Study in Thiru. Duraimurugan, [Mobile No: 078454 16243] farmer in Village of Kanmaniyapuram, Kadayanallur Taluk, Tirunelveli District. The case study revealed that, the benefit-cost ratio is 1:1.4 that means, if the farmer will spend one rupee the profit is rupee 1.4. In fact, that the farmer has been really struggling with the Break-Even Point. They face huge loss owing to poor yield. He must modify their production pattern and verify each cost component, which component to be minimize and which inputs might add to get higher profit with lower cost production.